New Caffeine Derivatives as Multitarget Agents for the Therapy of Alzheimer’s Disease - Biscussi, Brunella (2022)
In this work we present the microwave-assisted synthesis and in vitro acetylcholinesteraseinhibition of a series of new caffeine derivatives. The design of these new compounds was inspiredby the caffeine–pyrrolidine hybrids that act as AChE inhibitors and nAChR activators, previouslyreported by our group. All of the new caffeine analogs inhibited AChE. Among them, the compound2b (1,3-dimethyl-7-(6-(piperidin-1-yl)hexyl)-3,7-dihydro-1H-purine-2,6-dione) showed the strongesteffect (IC50 = 0.17 µM) on AChE, with higher potency than caffeine–pyrrolidine hybrids. Thesepreliminary studies suggest that these new compounds might be interesting multifunctional drugsdestined to stimulate cholinergic signage.